Using Peer Review for Student Performance Enhancement: Experiences in a Multidisciplinary Higher Education Setting. - Serrano-Aguilera, Juan José; Tocino-Sánchez, Alicia; Fortes-Rodríguez, Sergio; Martín-Fernández, Cristian; Mercade-Mele, Pere; Moreno-Sáez, Rafael Jesús; Muñoz-Gallego, Antonio Jesús; Palomo-Hierro, Sara; Torres-Signes, Antoni (MDPI, 2021)
Nowadays one of the main focuses of the Spanish University system is achieving the active learning paradigm in the context of its integration into the European Higher Education Area. This goal is being addressed by means of the application of novel teaching mechanisms. Among a wide variety of learning approaches, the present work focuses on peer review, understood as a collaborative learning technique where students assess other student’s work and provide their own feedback. In this way, peer review has the overarching goal of improving the student learning during this process. Peer review has been successfully applied and analyzed in the literature. Indeed, many authors also recommend improving the design and implementation of self and peer review, which has been our main goal. This paper presents an empirical study based on the application of peer review assessment in different higher education BSc and MSc courses. In this way, six courses from different studies at the University of Malaga in Spain are subject to the application of peer review strategies to promote student learning and develop cross-wise skills such as critical thinking, autonomy and responsibility. Based on these experiences, a deep analysis of the results is performed, showing that a proper application of the peer review methodology provides reliable reviews (with close scores to the ones from the teacher) as well as an improvement in the students’ performance.
Keywords: Investigación activa en educación; Enseñanza superior - Investigación; Peer assessment; Peer review; Collaborative evaluation; Higher education; Rubric